Burden of Invasive Methicillin‐Resistant Staphylococcus aureus Infections in Nursing Home Residents. Issue 8 (10th August 2018) - Grigg, Cheri; Palms, Danielle; Stone, Nimalie D.; Gualandi, Nicole; Bamberg, Wendy; Dumyati, Ghinwa; Harrison, Lee H.; Lynfield, Ruth; Nadle, Joelle; Petit, Susan; Ray, Susan; Schaffner, William; et al.
Abstract : Objectives: To describe the epidemiology and incidence of invasive methicillin‐resistant Staphylococcus aureus (MRSA) infections in nursing home (NH) residents, which has previously not been well characterized. Design: Retrospective analysis of public health surveillance data. Setting: Healthcare facilities in 33 U.S. counties. Participants: Residents of the surveillance area. Measurements: Counts of NH‐onset and hospital‐onset (HO) invasive MRSA infections (cultured from sterile body sites) identified from the Centers for Disease Control and Prevention Emerging Infections Program (EIP) population‐based surveillance from 2009 to 2013 were compared. Demographic characteristics and risk factors of NH‐onset cases were analyzed. Using NH resident‐day denominators from the Centers for Medicare and Medicaid Services Skilled Nursing Facility Cost Reports, incidence of NH‐onset invasive MRSA infections from facilities in the EIP area was determined. Results: A total of 4, 607 NH‐onset and 4, 344 HO invasive MRSA cases were reported. Of NH‐onset cases, median age was 74, most infections were bloodstream infections, and known risk factors for infection were common: 1, 455 (32%) had previous MRSA infection or colonization, 1, 014 (22%) had decubitus ulcers, 1, 098 (24%) had recent central venous catheters, and 1, 103 (24%) were undergoing chronic dialysis; 2, 499 (54%) had been discharged from a hospital in the previous 100 days. The in‐hospital case‐fatality rate was 19%. The 2013 pooled mean incidence of NH‐onset invasive MRSA infections in the surveillance area was 2.4 per 100, 000 patient‐days. Conclusion: More NH‐onset than HO cases occurred, primarily in individuals with known MRSA risk factors. These data reinforce the importance of infection prevention practices during wound and device care in NH residents, especially those with a history of MRSA infection or colonization.